PENGEMBANGAN MODEL PEMBELAJARAN HUMANIS DALAM PENDIDIKAN KARAKTER PADA MADRASAH IBTIDAIYAH - Kristiarso Kristiarso (Jurnal Penelitian Agama, 2015)
Abstract: This study aimed to: (1) get a humanist leaming model in character education at the madrasah level; (2) determine the effectiveness of humanist leaming model in instilling the values of the characters in self-leamers in madrasah; (3) determine the response of students to the humanistic leaming model. The results of the analysis of the model shows a model function quite well during limited testing or during implementation. The results of the analysis of the effectiveness of the model shows that the model meets the criteria very effective. Analysis of the study show that the output values are positive characters began to develop in the course of the trial and begin to be entrenched in self-leamers during implementation. Results of the analysis showed that all aspects practicality measurement models belong to the very practical criteria. The analysis shows that the validity of all validator states that the humanistic leaming model in character education in the madrasah and the assessment instruments have been prepared on the basis of reasoning that rationally the theory that a strong and relevant. T-test results through the method of paired t-test showed that there were significant differences between the characters leaming in character education in madrasah. These results indicate that the effective use of humanist leaming in support before and after the implementation of humanist character education in the madrasah Keywords: Humanist Education, Character Education